Glutamate - Ottersen, O. P. (Ole P.); Storm-Mathisen, Jon (Handbook of chemical neuroanatomy, 2000)
The volume presents a comprehensive and up-to-date treatise of the glutamatergic synapse and its environment. Particular emphasis is on the localizations of the molecular constituents of the synaptic machinery. Immunogold and other high-resolution methods are used extensively. Each chapter presents new data that have not previously been reviewed. The material presented forms the basis for work directed to understanding the functional properties of excitatory synapses in greater depth, to discover mechanisms of neurological and psychiatric disorders and novel methods for treatment. Chapter 1 deals with the transmitter molecule itself, mechanisms of release and pathways for glutamate synthesis. The anatomy of glutamatergic nerve projection pathways in different brain regions is dealt with. In Chapter 2, focus is on aspartate, the enigmatic congener of glutamate, and its possible role in excitatory neurotransmission. Chapters 3 through 6 deal with glutamate receptors. Metabotropic glutamate receptors are presented in Chapter 3. Chapter 4 presents an in situ hybridization atlas of the different classes of ionotropic glutamate receptors. The localizations of these receptors at the regional and synaptic level are presented in Chapter 5. The ways in which the receptors are brought to the synapse and held in position are the subject of Chapter 6. Chapter 7 deals with the enzymes responsible for formation and catabolism of glutamate. In Chapter 8, the regulation of extracellular glutamate levels by glutamate transporters is discussed. The final two chapters of the volume focus on two "model synapses" that, due to special features, lend themselves particularly well to demonstrating properties of glutamatergic synapses. The hair cell-to-afferent nerve terminal synapses in the inner ear (Chapter 9), with their supporting cells, share essential properties with glutamatergic synapses in the central nervous system. The salient features of the latter are illustrated by the synapses of the giant reticulo-spinal axons of the lamprey, used to unravel molecular mechanisms of the cycling of synaptic vesicles (Chapter 10)